Analisa Pengaruh Citra Merek dan Kualitas Produk Terhadap Minat Beli Produk Xiaomi (Studi Kasus pada Mahasiswa STIE HAS Bukittinggi) - Siska, Adilla Juita (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
The research that has been carried out aims to find out how much influence the Brand Image and Product Quality have on the Interest in Buying Xiaomi Products. In this study, the author utilizes primary data that has been obtained from the results of research by distributing questionnaires or a list of structured statements and answered directly by respondents. In this research, the population is STIE Haji Agus Salim Students, Bukittinggi, which numbered 396 people. For sampling, Slovin formula is used, so that the sample obtained is 80 people and given a questionnaire, then the data is processed using SPSS version 17 and the stages of testing instruments in this study used testing validity and reliability testing using binary logistic regression analysis. The results of the analysis show that Brand Image and Product Quality have a positive and significant effect on Buying Interest Xiaomi Products. While Product Quality is the most dominant variable that influences Buying Interest.